Genome-wide identification and functional characterization of wheat Brassinazole-resistant transcription factors in response to abiotic stresses and stripe rust infection - Zhang, Peng; Yan, Hanwen; Liu, Yu; Chai, Yi (Frontiers in Plant Science, 2023)
Brassinazole-resistant (BZR) transcription factors (TFs) are key players in brassinolides (BRs) signaling pathway, which is widely involved in regulating plant growth and development, as well as in plant responding to a variety stresses. Despite their critical roles, little is known about BZR TFs in wheat. In this study, we performed genome-wide analysis of BZR gene family from wheat genome, and 20 TaBZRs were identified. Based on the phylogenetic relationships of TaBZR and BZRs from rice and Arabidopsis, all BZR genes were clustered into four groups. The intron-exon structural patterns and conserved protein motifs of TaBZRs showed high group specificity. TaBZR5, 7, and 9 were significantly induced after salt, drought treatment, and stripe rust infection. However, TaBZR16, which was significantly upregulated under NaCl application, was not expressed during wheat-stripe rust fungus interaction. These results indicated that BZR genes in wheat play different roles in response to various stresses. The results of this study will lay a foundation for further in-depth functional studies of TaBZRs and will provide information for the breeding and genetic improvement of wheat against drought and salt stresses.